Définir le paradoxe : de la logique à la linguistique - Wołowska, Katarzyna (Studia Romanica Posnaniensia, 2005)
The linguistic paradox - considered in a perspective of the discourse analysis - appears to be a mechanism rooted in two relations: the oppositional one (contradiction or contrariness) and the junction obtaining between the same components. The interpretation of the paradox can also be implied (or, sometimes, even forced) by using terms or markers directly stating its presence paradoxical, paradoxically, it seems paradoxical that, etc.); still, each componential opposition can be neutralized in the discourse, which makes contradiction and contrariness canceled on the level of semantic interpretation to have later the paradoxical sequence integrated into the "doxical perspective".